2002
DOI: 10.1016/s0022-2836(02)00522-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model of DNA Replication in Eukaryotic Organisms

Abstract: (J.B.) and abensim@pasteur.fr (A.B.) We formulate a kinetic model of DNA replication that quantitatively describes recent results on DNA replication in the in vitro system of Xenopus laevis prior to the mid-blastula transition. The model describes well a large amount of different data within a simple theoretical framework. This allows one, for the first time, to determine the parameters governing the DNA replication program in a eukaryote on a genome-wide basis. In particular, we have determined the frequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
129
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(138 citation statements)
references
References 46 publications
9
129
0
Order By: Relevance
“…To avoid the random gap problem, it has been argued that there must be some mechanism to coordinate origin firing so as to avoid large random gaps 22 . Surprisingly, in two cases in which the distribution of origin firing has been carefully examined -frog embryo extracts and fission yeast -the distribution was in fact random and large random gaps were observed 8,9,23,24 .…”
mentioning
confidence: 99%
“…To avoid the random gap problem, it has been argued that there must be some mechanism to coordinate origin firing so as to avoid large random gaps 22 . Surprisingly, in two cases in which the distribution of origin firing has been carefully examined -frog embryo extracts and fission yeast -the distribution was in fact random and large random gaps were observed 8,9,23,24 .…”
mentioning
confidence: 99%
“…Although most of the applications of the KJMA model have been to the study of phase transformations in threedimensional systems, similar ideas have been applied to a wide range of one-dimensional problems, such as Rényi's car-parking problem [12] and the coarsening of long parallel droplets [13]. Recently, we have shown that the onedimensional KJMA model can also be used to describe DNA replication in higher organisms [19]. Briefly, in higher organisms (eukaryotes), DNA replication is initiated at multiple origins throughout the genome.…”
Section: Island-to-island (I2i)mentioning
confidence: 99%
“…Recently, Herrick et al used a more efficient algorithm [19]. Specifically, they recorded the positions of moving island edges only.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methods include dynamic molecular combing (meniscus moving on a coverslip [14]), spin-stretching [8,9], the evaporation of small droplets of DNA solutions [15,16], the stretching of DNA with a cover slip [17], the mechanical movement of a *Corresponding author (email: 51888lyy@sina.com) meniscus [18], droplet motion driven by a nitrogen gas flow [19], the precise control of the meniscus motion [20], the ordered stretching of DNA between micro fabricated polystyrene lines [21], the moving droplet method [22] and aligning DNA molecules on a SiO 2 surface using a diamond-like carbon (DLC) thin film [23]. Combined with other techniques, the applications of the molecular combing method can be widened to include positioning genes on chromosomes [14], the genomic studies of DNA replication [24], the observation of transcription on a single combed DNA [25], the study of the interaction between DNA and enzymes [26,27] and the self-organized DNA network between two cover slips [28].Eukaryotic genes do not exist as naked DNA molecules in the nucleus of a cell. Instead, they combine with particular proteins, especially the basic proteins called histones, to form a substance known as chromatin [29].…”
mentioning
confidence: 99%